Public health and plain packaging of tobacco: An intellectual property perspective - Thamara Romero (South Centre, 2020)
In 2018, a World Trade Organization (WTO) Panel ruled that plain packaging of tobacco products was consistent with Australia's obligations under the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and was in the interest of public health. Plain packaging restricts the use of logos, colours and brand images to reduce the demand for and consumption of tobacco products by diminishing their advertising appeal. This paper discusses the intellectual property aspects triggered by the implementation of plain packaging, examines the best practices for its implementation and provides analysis of Australia's case from the public health perspective. It also highlights the main arguments used in the dispute against Australia and provides practical guidance for WTO Members on implementing measures to protect public health.
Keywords: 300; Australia; Canada; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; Framework Convention on Tobacco Control (FCTC); Free Trade Agreements (FTAs); Health; India; Intellectual Property; International Investment Agreements (IIAs); Norway; Philip Morris; Plain Packaging; Public Health; Tobacco Products; TRIPS; Uruguay; WHO; World Health Organization (WHO); World Trade Organization (WTO); WTO